Bacteriological Pattern of Pediatric Sepsis in PICU of A Tertiary Care Hospital - Ilham Imam; Mumtahena Mahmuda; Mir Mosharof Hossain; Md Mujammel Hoque; Hasina Momotaj Hira (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Pediatric and neonatal sepsis are one of the main causes of mortality in neonatal and Pediatric Intensive Care Units (PICU) of developing countries. To evaluate the bacteriological pattern of pediatric sepsis in a newly set PICU. The etiopathogenesis and medication susceptibility pattern of causative agents need to be reviewed frequently due to the continuously evolving bacteriologic profile of childhood sepsis. Materials and methods: This descriptive observational study was conducted in the PICU of Chattogram Medical College Hospital, Chattogram. The study was carried out from March 2017 to February 2018. According to inclusion/exclusion criteria 146 pediatric patients were taken as sample by purposive sampling. Data were collected by face-to-face interview from the parents or caregivers. Clinical examination was done by researcher herself, blood culture reports and retrospective data were collected from hospital records. The blood culture was done in the laboratory in the department of microbiology, and in the department of clinical pathology, Chattogram Medical College Hospital, for further processing. Results: Among 146 respondents the frequency of culture positive specimens was 19%. Among the culture positive patients, majority (48%) fall in infant age group. Male to female ratio were 1.05:1, 1.24:1and 1.3:1 in 2016, 2017 and 2019 respectively. Majority of the patients (67.2%) were from rural area in all 3 years. There was no significant difference in sex and area of living distribution between the years. Regarding different ICU modalities among the culture positive patients, oxygen hood was used for (48.3%), Cardiac monitor (24.1%) ventilator (44.8%) and inotrope (24.1%). There was no significant difference in provision of different ICU modalities between culture positive and negative patients. Among the 27 culture positive samples, majority of the isolated micro-organisms were gram negative bacteria (86.4%) followed by gram positive bacteria (13.6%) with Acinetobacter sp. (29.6%), Pseudomonas sp. (25.9%) and Klebsiella sp. (25.9%) predominating. Conclusion: This study was undertaken in order to document the most common types of pathogens causing sepsis in children admitted in the newly established Pediatric Intensive Care Unit (PICU) of Chattogram medical college hospital and their outcome. From the current study, we found that majority of the organisms were gram negative in the PICU. If a specialized center like PICU has its own microbiological and antibiotic sensitivity pattern, then they can have their own protocol to establish. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 62-65